Reflections on Transformative Experiences with Mathematical Inquiry: The Case of Christine. Issue 1 (2nd January 2017) - Flores, Alfinio; Phelps, Christine M.; Jansen, Amanda
Abstract: We present a first-hand, longer-term account of one student's (Christine's) experiences in and after a mathematics inquiry course. In this course, students actively posed problems, conducted their own mathematical explorations, and wrote journal entries about their experiences. During the course, Christine found that inquiry helped her develop mathematical content knowledge and a deeper understanding of the nature of research. After the course, Christine became a mathematics education faculty member in a mathematics department and reports that the course impacted the way she teaches mathematics. This provides an illustrative case of the potential long-lasting benefits of an inquiry course.